Low Tesla Magnetic Resonance Imaging In Spinal Injuries-A study from western Maharashtra - Shaha, Pramod; Ruchi,; Sawarkar, Kapil P.; Kumar, Snehil; Phatak, Juilee (International Journal of Psychosocial Rehabilitation, 2020)
Due to mechanical development of world and use of vehicles, spinal trauma is most commonly caused by road traffic accident followed by at work places, sports and fall at home.MRI being the modality of choice for spinal cord injuries followed by CT for bony injuries.Methods-Total 120 patients of all ages and both sexes were included in this study, who came to Krishna Institute of Medical Sciences, Karad with history and complaints of spinal trauma.Results-Low Tesla MR imaging is also useful in depicting different types of acute spinal cord injuries like cord compression, hemorrhage,cord transaction, etc.As compared to 1.5 Tesla MR imaging, 0.3 Tesla MRI machine can also give enough diagnostic information about spinal cord injuries at low cost without significantly affecting the quality of diagnosis.Conclusion-MRI is the modality of choice for spinal cord injuries.0.3TeslaMRI is also of a diagnostic value in spinal cord injuries as comparedto high 1.5Tesla MRI.